Systemic Banking Crises Database : An Update - Valencia, Fabian (IMF Working Papers; Working Paper ;, 2012)
We update the widely used banking crises database by Laeven and Valencia (2008, 2010) with new information on recent and ongoing crises, including updated information on policy responses and outcomes (i.e. fiscal costs, output losses, and increases in public debt). We also update our dating of sovereign debt and currency crises. The database includes all systemic banking, currency, and sovereign debt crises during the period 1970-2011. The data show some striking differences in policy responses between advanced and emerging economies as well as many similarities between past and ongoing crises.